(untitled) (Baghdad Science Journal, 2021)
Echinococcosis is a zoonotic disease caused by the larval stage of the tapeworm Echinococcus granulosus. This disease is an important public health and a significant economic issue in Iraq, where the lungs and livers are the popular places of infection. The aim of the current study focused on using the molecular techniques in the detection of an E. granulosus strain that causes cystic echinococcosis to human, sheep and cattle in Thi-Qar province, Iraq. In the current study, thirty isolates of E. granulosus were collected from 10 human hydatid cysts through surgery done at Al-Hussein Imam Teaching Hospital in Thi-Qar province and 10 sheep with 10 cattle hydatid cysts were obtained from the slaughterhouse in Thi-Qar province, Southern of Iraq to identify strains of E. granulosus which infect human and other intermediate hosts (sheep and cattle). The molecular study was carried out on the isolates and a specific primer set for the mitochondrial dehydrogenase NADH subunit 1 (NAD1) gene was used. This primer set was amplified 400 bp of the NAD1 gene in all selected isolates. The PCR products for the twelve selected isolates of E. granulosus (4 isolates per intermediate host) were sequenced and the results for these twelve isolates showed that all sequenced isolates, except one isolate Eg_5, belonged to the sheep strain G1 and a slight genetic diversity was observed with the reference sequences of the strain G1. The exception was in the isolate Eg_5 isolated from a cattle liver, which was similar to the buffalo strain G3. This study concludes that the common E. granulosus strain in Thi-Qar province is G1.